Encyclopedia of intelligence and counterintelligence - Carlisle, Rodney P.; Albion, Alexis (Routledge, 2015)
From references to secret agents in The Art of War in 400 B.C.E. to the Bush administration's ongoing War on Terrorism, espionage has always been an essential part of state security policies. This illustrated encyclopedia traces the fascinating stories of spies, intelligence, and counterintelligence throughout history, both internationally and in the United States. Written specifically for students and general readers by scholars, former intelligence officers, and other experts, Encyclopedia of Intelligence and Counterintelligence provides a unique background perspective for viewing history an.